Influência da intensidade do exercício sobre a pressão arterial pós-exercício em diferentes genótipos do polimorfismo - Fernandes, Manuella de Oliveira (2014)
The post-exercise hypotension (HPE) is considered a non-pharmacological strategy adopted for the reduction of blood pressure (BP). However, some factors may influence the HPE, among them stand out the genetic mutations that are responsible for 30% of the predisposition to cardiovascular disease. In this regard, recent studies have directed attention to better understand how the presence of genetic polymorphisms, such as I / D angiotensin-converting enzyme (ACE) gene may influence the pressure response after performing the exercise. The objective of this study was to analyze the influence of the ACE ID polymorphism on PEH in different intensities as well as the possible attenuation of the reactivity of BP after a cardiovascular stress test in normotensive, young and physically active men. Voluntarily participated in the study 26 young normotensive adults, male and were grouped into two genotype groups (DD = 11, ID / II = 15). All underwent a maximal exercise session of 1.600 meters, on the athletics track, in order to estimate the anaerobic threshold and the indirect VO2max. Subsequently, randomly assigned to three experimental sessions of 20 minutes was carried out: # 1. Moderate Test at 6% below the anaerobic threshold; # 2. Intense Test at 6% above the anaerobic threshold; # 3. Control session without exercise. All sessions were composed of five times, being: 1. Previous PA measurement (rest) for 20 min; 2. Realization of the sessions; 3. Record of post-exercise BP during 60 minutes; 4. Realization of cardiovascular stressor test (CPT); 5. Measurement of PA for over 30min. The main result was that moderate exercise resulted HPE, independent of genotypic group, especially for systolic BP at 45 and 60 min (p . 0.05). This reduction persisted after CPT only for allele carrier group |I| (p . 0.05). Thus, it was concluded that moderate intensity was more effective to cause HPE and the carrier group allele |I| showed effective attenuation of pressor reactivity.